Estudo de propriedades magnéticas da ferrita multiferróica hexagonal LuFeO3 através de cálculos baseados na teoria do funcional da densidade - Melo, Ailson Tavares de (2018)
In this work was performed a theoretical study on the electronic and magnetic properties of hexagonal ferrites LuFeO3 (h-LuFeO3). Was employed the Full Potential Linearized Augmented Plane Wave (FPLAPW) electronic structure calculation method, based on the density functional theory (DFT) and implemented in Elk code. The calculations were performed with experimental ferroelectric h-LuFeO3 structure. First, we simulated the collinear magnetic spin configurations as ferromagnetic (FM) and the antiferromagnetic of type A (A-AFM) and of type G (G-AFM). The electronic exchange and correlation effects was treated by LSDA approach and was accounted the spin-orbit coupling (SOC). The G-AFM state was found to be the ground state between later three collinear magnetic structures simulated (FM, A-AFM and G-AFM). This result is in agreement with that previously published. Based on this ground state magnetic structure, we analyzed which is the best + method (around mean field (AMF), fully-localized limit (FLL) and of the interpolation (INT)) to be applied to our system. The INT method was found as more appropriated to treat the double counting correction in + method for the h-LuFeO3 system. As a second step of calculation in this work were simulated the , , , e non-collinear magnetic structures that have been pointed in the literature as the ground state of h-LuFeO3. The electronic XC effects were treated by LSDA approach and was accounted the SOC. The latter was responsible for canting of the spin moment in magnetic structures that this feature is allowed by symmetry ( , , e ). The spin configuration should be the ground state by our DFT- LSDA+SOC calculations. The total and partial density of states revealed that Fe 3d and O 2p states are strongly hybridized in the top of valence band and bottom of the conduction band in h-LuFeO3 compound. Was not found significate difference between the electronic structure of G-AFM and states. This conclusion is result of higher degree of magnetic frustration of the studied system. Was verified that the band gap energy is dependent on spin configuration, besides of dependence with the electronic XC scheme employed.